EFFICACY AND SAFETY OF RHO KINASE INHIBITOR EYEDROPS FOR THE TREATMENT OF OPEN-ANGLE GLAUCOMA AND OCULAR HYPERTENSION: A LITERATURE REVIEW - Sahar Salim Saleh Alatas; Astrianda Nadya Suryono (Majalah Oftalmologi Indonesia, 2023)
Introduction: Reduction of intraocular pressure (IOP) is the only proven method to treat glaucoma. Studies on aqueous humor dynamics have contributed to our understanding of aqueous outflow mechanisms that have led to the discovery of new drugs from Rho Kinase Inhibitors (RKI). Aims: To evaluate the efficacy and safety of RKI for treating open-angle glaucoma (OAG) and ocular hypertension (OHT). Methods: Literature searching was conducted through PubMed, ScienceDirect, Google Scholar, and Springer Link. Search terms included: “Open Angle Glaucoma”, “Ocular Hypertension”, and “Rho Kinase Inhibitors”, which provides for Netarsudil (AR-13530), Ripasudil (K-115)" or any relevant synonym. Validity was assessed using version 2 of the Cochrane risk of bias tool for randomized trials (RoB 2). Efficacy was evaluated by reported mean change IOP from baseline. Safety was assessed by adverse events experienced during the treatment course. Results: Eight randomized clinical trial studies fulfilled our inclusion criteria (four studies using Netarsudil 0.02% and four using FCNL as the primary treatment). IOP reduction from Netarsudil 0.02% was not inferior to Timolol 0.5%. Meanwhile, IOP reduction from FCNL class was statistically superior to its active component alone. The most common adverse events of Netarsudil 0.02% and FCNL were conjunctival hyperemia, cornea verticillate, and conjunctival hemorrhage. FCNL showed additional adverse events of site hyperemia and pain. Conclusion: Netarsudil 0.02% and FCNL can be reliable IOP control medications. The adverse events were tolerable.